2014
DOI: 10.1088/0963-0252/23/5/054010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen gas on characteristics of self-organized luminous pattern formation observed in an atmospheric dc glow discharge using a liquid electrode

Abstract: Self-organized luminous pattern formation is observed in the liquid surface of an atmospheric dc glow discharge using a liquid electrode with a miniature helium flow. The factors affecting pattern formation are the gap length, discharge current, helium mass flow rate and polarity. The pattern shape depends on the conductivity and temperature of the liquid electrode. A variety of patterns were observed by changing the conductivity and temperature of the liquid. We clarified that the self-organized pattern forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 34 publications
6
72
0
2
Order By: Relevance
“…As for figure 18, a DC glow discharge of He over a liquid anode is used. For both, a 1% NaCl solution or tap water anode, the self-organization of patterns tends to appear for larger inter-electrode spacing and high currents [167,169]. The emergence of patterns was also found to be dependent on the axial flow rate, with lower flow rates favoring the formation of patterns; as well as on the liquid temperature, par ticularly on the vapor pressure [167].…”
Section: Patterns On Liquid Anodesmentioning
confidence: 88%
See 3 more Smart Citations
“…As for figure 18, a DC glow discharge of He over a liquid anode is used. For both, a 1% NaCl solution or tap water anode, the self-organization of patterns tends to appear for larger inter-electrode spacing and high currents [167,169]. The emergence of patterns was also found to be dependent on the axial flow rate, with lower flow rates favoring the formation of patterns; as well as on the liquid temperature, par ticularly on the vapor pressure [167].…”
Section: Patterns On Liquid Anodesmentioning
confidence: 88%
“…Such response is qualitatively maintained for higher flow rates of incident gas. Moreover, further investigations show the emergence of anode patterns due to the diffusion of air on a He discharge, whereas no patterns are observed when a sheath flow of N 2 (which limits the entrainment of O 2 into the discharge) is used [167].…”
Section: Patterns On Liquid Anodesmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma jets are normally excited by pulsed voltages with kilohertz repetition frequencies as well as sinusoidal voltages in the kilohertz-to-megahertz range. [15][16][17][18][19][20] Besides, related studies have been reported with concern of the discharge characteristics, 21 the discharge mechanism, 22,23 and the analysis of plasma products, 24 etc. Recently, the comparisons of pulsed and sinusoidal plasma jets in the gas phase have been reported, 15,25 and the results show that pulsed excitation is more efficient to produce energetic electrons rather than heat the gas, 25 and hence more reactive species can be generated in pulsed plasmas.…”
Section: Introductionmentioning
confidence: 99%